Collaborative governance in CSR management program for slum area rehabilitation - Muhammad Roisul Basyar; Anggraeny Puspaningtyas (Universitas Merdeka Malang, 2022)
This study aims to explain how the skills needed for successful collaboration between the government, the private sector, and the community are as a solution for social rehabilitation of slum settlements. The case chosen was a collaboration between PT Astra International, the sub-district government, and the people of the East Keputih Tegal Sub district, Surabaya City which is a CSR fund management program. This study uses a qualitative descriptive method using primary data collection techniques (interviews, observation and documentation). The theory used in this research is collaborative governance skills according to (Donahue Zeckhauser, 2011). The results show that the success of Collaborative Governance that occurs between the Government, PT. ASTRA and the community can run optimally because they are able to collaborate in 4 types, namely, a) Collaboration for Productivity, b) Collaboration for Information; c) Collaboration for Legitimacy Collaborative governance; and d) Collaboration for Resources. From the 4 types of collaboration that the researcher analyzed, all collaboration skills that occur are in accordance with the 8 skills proposed by (Donahue Zeckhauser, 2011). The success of this collaboration is because the sub-district government is able to delegate several functions to PT ASTRA and the community. In addition, community participation can be facilitated from the beginning of the program to implementation. PT ASTRA is very professional in carrying out the delegation function given by the sub-district government and the Surabaya City Government.